Retrospective analysis of the epidemiological profile of patients undergoing breast reconstruction in a public hospital in Northeastern Brazil - de Lima Ferreira Filho, Darley; Cristina Ferraz de Lucena Ferreira, Nancy; de Lucena Ferreira, Thais (Mastology, 2025)
Breast reconstruction is a right guaranteed by the public health system to patients undergoing mastectomy. The present study aimed to understand the epidemiological profile of women with breast cancer who underwent breast reconstruction at a referral hospital in the Northeast region of Brazil. Methods: Observational, retrospective study with an analytical character and descriptive approach. Data were collected through a sociodemographic questionnaire and clinical-surgical history, and were subsequently analyzed using SPSS version 18, with the percentages of the categories evaluated by the χ2 test, considering a significance level of 5%. The comparison of the analyses was significant (p<0.005), demonstrating that the profile described was the most frequent in the group of patients evaluated. Results: A non-probabilistic sample of 400 medical records was obtained from a public referral hospital in the unified health system of the Northeast Region. The majority had a mean age between 46 and 59 years (45.3%) and brown skin color (61.1%), and were married (79.1%), with education up to high school (60.7%); they were housewives (45.0%), non-smokers (84.9%), non-alcohol drinkers (94.9%) and underwent immediate reconstruction after mastectomy (70.3%). Conclusions: The findings support that patients with high education levels are likely to undergo immediate breast reconstruction, indicating that socioeconomic level significantly influences the rates of breast reconstruction after radical or conservative breast surgery.